Finding proactive features in labour market policies: a reflection based on the evidence - Malo, Miguel Angel (Geneva, 2018)
"Proactive labour market policies consist of active labour market measures or other interventions that are implemented preemptively, with the aim of protecting people against a wide range of labour market problems and economic shocks. Proactive policies will be important in facing the challenges of the future of work. The discussion is based on a review of effective active labour market policies (ALMPs) including training, public works, direct job creation, employment incentives and job counselling and other labour market services; specifically, it examines how ALMPs and their integration with income support programmes can be used in a proactive manner. Throughout the paper, differences between developed and developing and emerging countries are considered. The paper suggests that policy implementation is crucial for a proactive approach, which can permit the use of complementary policies and programmes with proactive and reactive features that support activation of the labour force. It argues that social dialogue may enhance the role of implementation variables, especially tripartite social dialogue at an aggregate level. A combination of policies in the context of social protection floors for developing countries and activation strategies for developed countries can also help in the transition to an effective proactive approach."